Community assistance for mover teachers through the lesson study-based opening class movement - Evi Suryawati; S. Syafrinal; Evfi Mahdiyah; H. Hermandra; Didi Muwardi; Tengku Firli Musfar (Universitas Muhammadiyah Malang, 2023)
The assistance for the Guru Penggerak (Mover Teachers) Community through the open class movement based on lesson study at SMPN 23 Pekanbaru was carried out from May to mid-September 2022, involving 32 teachers who acted as model teachers and observers. This assistance is carried out based on the Lesson Study (plan-do-see) stage. Implementation of the open class movement was conducted in four subjects: Science, Mathematics, English and Islam. In the Plan stage, the core team discusses lesson design, innovation, and agrees on a schedule and division of tasks. In the Do stage (open class), the model teacher carries out learning which is attended by observers and committee representatives. During learning activities, observers observe student learning activities. The See stage (reflection), the whole teams evaluate the implemented learning. The mentoring result show that students appear to be active and enthusiastic about learning. Teachers can work with colleagues to implement classroom learning by focusing on active, creative, effective, innovative, and fun learning. This Open Class Movement will be continued in five subjects so the entire community of subject teachers can work together in the learning community to improve the quality of learning in the Independent Curriculum Implementation, especially by the Mover Teachers.